Pemanfaatan Wordwall dalam Pembelajaran Blended Learning - Harni, Harni; Epitasari, Eptasari; Mudrika, Mudrika; Arif, Nur Cholis (South Sulawesi Education Development, 2024)
This research evaluates the use and benefits of Wordwall in blended learning, which combines face-to-face and online methods to increase educational flexibility and accessibility. The Systematic Literature Review (SLR) method is used to analyze journal articles from various databases such as Research Gate, Google Scholar, and ERIC. The nine most relevant articles were analyzed, showing that Wordwall is effective in increasing students' learning motivation, participation and learning outcomes. Wordwall, a browser-based application, provides interactive activities that enrich the learning experience and build positive traits such as discipline and responsibility. These findings recommend the use of Wordwall to maximize learning outcomes in a blended learning context, both online and offline